High Transition Temperature Superconductor/Insulator Bilayers for the Development of Ultra-Fast Electronics - Sirena, Martin (2013)
High transition temperature superconductor (HTc)/SrTiO3 (STO) bilayers were fabricated by sputtering deposition on (100) STO substrates. Their transport and morphological properties were characterized using conductive atomic force microscopy. The STO barriers present good insulating properties, with long attenuation lengths (λ ∼ 1 nm) which reduce the junction resistance and increase the operating critical current. The samples present roughness values smaller than 1 nm, with an extremely low density of surface defects (∼5 × 10−5 defects/μm2). The high control of the barrier quality over large defect free surfaces is encouraging for the development of microelectronics devices based in HTc Josephson junctions.